Prevalencia de anemia en niños de 6 meses a 5 años de edad de la zona urbana de la parroquia Cumbaratza. año 2015 - Meza Ochoa, Denis Enid (2016)
The present investigation was to determine the prevalence of anemia in children aged 6 months to 5 years old in the urban area of the Cumbaratza parish. For the development of study types, cross-sectional, observational field research, descriptive, retrospective, prospective and literature was used. For information the technique used was the survey with a questionnaire as an instrument that mothers of children and direct observation with an observation guide instrument applied in the review of medical records was applied. The results indicated a prevalence of anemia of 53,4%; between the data according to demographic characteristics they are: the age of 4 to 4 11m 29d with 46,15%, regarding the 58,97% male, ethnicity predominates mestizo with 100%, socioeconomic status this population is the lowest average with 61,54 %, among the results of the degrees of anemia are; 64,10% the mild anemia with hemoglobin level of 10 to 10,9 g/dl and moderate the 35,90%, with a range of 7 to 9,9 g/dl of hemoglobin level, after obtaining the results an action plan was implemented through educational activities, workshops, home visits, children with severe disease received medical treatment. It was concluded that the prevalence of anemia was 53,42%.